2012
DOI: 10.5194/acp-12-7413-2012
|View full text |Cite
|
Sign up to set email alerts
|

α-pinene photooxidation under controlled chemical conditions – Part 2: SOA yield and composition in low- and high-NO<sub>x</sub> environments

Abstract: Abstract. The gas-phase oxidation of α-pinene produces a large amount of secondary organic aerosol (SOA) in the atmosphere. A number of carboxylic acids, organosulfates and nitrooxy organosulfates associated with α-pinene have been found in field samples and some are used as tracers of α-pinene oxidation. α-pinene reacts readily with OH and O 3 in the atmosphere followed by reactions with both HO 2 and NO. Due to the large number of potential reaction pathways, it can be difficult to determine what conditions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 52 publications
15
141
2
Order By: Relevance
“…As shown in Table 1, the Y values of toluene, TMB, isoprene, and α-pinene SOA ranged from 5 to 15, 6 to 8, 1 to 5, and 14 to 36 %, respectively. Except isoprene SOA, the SOA yields in this study were consistent with those reported in previous studies (Eddingsaas et al, 2012a;Healy et al, 2008;Odum et al, 1996;Sato et al, 2007). Our SOA yields for isoprene SOA were lower than those reported in other studies (Carlton et al, 2009;Xu et al, 2014) because the temperatures in our outdoor experiments were higher than those sourced from indoor chambers.…”
Section: Dtt Activity Of Soasupporting
confidence: 77%
“…As shown in Table 1, the Y values of toluene, TMB, isoprene, and α-pinene SOA ranged from 5 to 15, 6 to 8, 1 to 5, and 14 to 36 %, respectively. Except isoprene SOA, the SOA yields in this study were consistent with those reported in previous studies (Eddingsaas et al, 2012a;Healy et al, 2008;Odum et al, 1996;Sato et al, 2007). Our SOA yields for isoprene SOA were lower than those reported in other studies (Carlton et al, 2009;Xu et al, 2014) because the temperatures in our outdoor experiments were higher than those sourced from indoor chambers.…”
Section: Dtt Activity Of Soasupporting
confidence: 77%
“…Indeed, there are several similarities between products formed from the photooxidation of α-pinene and m-xylene. For instance, a large portion of α-pinene and m-xylene oxidation products under both RO 2 + HO 2 and RO 2 + NO pathways are ring-breaking products with a similar carbon chain length (Eddingsaas et al, 2012;Vivanco and Santiago, 2010;Jenkin et al, 2003). As a result of this similarity, products from both SOA systems may interact with the same cellular targets and induce similar cellular pathways, resulting in a similar response regardless of precursor identity and formation condition.…”
Section: Discussionmentioning
confidence: 96%
“…The selected biogenic precursors include isoprene, the most abundant non-methane hydrocarbon (Guenther et al, 2006); α-pinene, a well-studied monoterpene with emissions on the order of global anthropogenic emissions (Guenther et al, 1993;Piccot et al, 1992); and β-caryophyllene, a representative sesquiterpene. Both monoterpenes and sesquiterpenes have been shown to contribute significantly to ambient aerosol (Eddingsaas et al, 2012;Hoffmann et al, 1997;Tasoglou and Pandis, 2015;Goldstein and Galbally, 2007). Similarly, the anthropogenic precursors include pentadecane, a long-chain alkane; m-xylene, a singlering aromatic; and naphthalene, a polyaromatic.…”
Section: W Y Tuet Et Al: Inflammatory Responses To Soa Generated Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In boreal forests, α-pinene is the most abundant monoterpene. It has been extensively studied in laboratory experiments during the past decades due to its large SOA formation potential (Hoppel et al, 2001; Lee and Kamens, 2005;Eddingsaas et al, 2012a). Several oxidation pathways are known (see Fig.…”
Section: A P Praplan Et Al: Elemental Composition and Clustering Bmentioning
confidence: 99%